The Dimensional Structure of Tourism Festival and Special Event Innovation and Their Impacts on Tourists’ Behavioral Intentions - Chaojun Li; Ping He (Discrete Dynamics in Nature and Society)
The tourism festival and special event innovation are the important factors influencing the creation of superior value, the achievement of customer loyalty, and profitable growth. Based on the perspective of product supply and consumer demand integration analysis, this paper constructed an integrated model of tourism festival and special event innovation and its impacts on tourists’ behavioral intentions. The basic data was obtained through the tourist survey on Zhangjiajie International Country Music Festival, and the exploratory factor analysis, confirmatory factor analysis, and structural equation modeling were used to empirically test the relationship between various dimensions of tourism festival and special event innovation and their impacts on tourists’ behavioral intentions. The results show the following: (1) tourism festival and special event innovation includes six dimensions of performance, accessibility, self-service technology, aesthetic environment, tourist community, and loyalty program; (2) performance, self-service technology, and aesthetic environment have a significant positive impact on overall innovation, while accessibility, tourist community, and loyalty program have no significant impact on overall innovation; and (3) overall innovation has a significant positive impact on tourists’ satisfaction, brand equity, and tourists’ behavioral intentions. Moreover, tourists’ satisfaction and brand equity play a partial intermediary role in the impacts of overall innovation on the tourists’ behavioral intentions. The article concludes with research limitations and future research directions.